Sistema de planificación de mantenimiento - Arias Peña, Dolores Mariana (2010)
This document describes the development aspects of information technology projects to be based on methodology Framework, which will manage the project, quality assurance and control personnel. The following sections describe the background to its creation and the steps to follow to develop the project